KANT'IN BİLGİ KURAMI VE SENTETİK ÖNERMELER - Veli Urhan (Felsefe Dünyası)
According to Kant, while one part of our knowledge relies on both senses and thought, the other part relies on thought only. Knowledge of phenomena within a space and time come through both senses and thought, whereas knowledge of non-phenomenal ideas like God, Soul, Universe comes merely through thought. All propositions stating the knowledge of phenomena are synthetic, which have a priori and a posteriori forms. That knowledge of phenomenal world is accepted as scientific knowledge depends on the fact that there are synthetic a priori propositions about the world. Physics is a science since it has both synthetic a priori and synthetic a posteriori propositions. Knowledge about ideas of metaphysical world relies only on thought because it is not Phenomenal. It can be said that metaphysics is a science only if synthetic a priori judgements can also be made in the metaphysical sphere. To Kant, this is possible only for pure practical reason, not for pure theoretical reason.